USPON AUTORITARIZMA NA ZAPADNOM BALKANU - Nikola Mladenovic (Srpska Politička Misao)
Book review: Florian Bieber. 2020. The Rise of Authoritarianism in the Western Balkans. Switzerland: Palgrave Macmillan, 155.